Ideological Conflict and Prejudice: An Adversarial Collaboration Examining Correlates and Ideological (A)Symmetries. Issue 1 (January 2021) - Stern, Chadly; Crawford, Jarret T.
In an adversarial collaboration, we examined associations among factors that could link ideological conflict—perceiving that members of a group do not share one's ideology—to prejudice and affiliation interest. We also examined whether these factors would possess similar ("symmetrical") or different ("asymmetrical") associative strength among liberals and conservatives. Across three samples (666 undergraduate students, 347 Mechanical Turk workers), ideological conflict was associated with perceived dissimilarity on political and nonpolitical topics, as well as negative emotions. Perceived political and nonpolitical dissimilarity were also associated with negative emotions, prejudice, and lower affiliative intentions among both liberals and conservatives. Importantly, however, perceived political dissimilarity was associated with negative emotions, prejudice, and lower affiliative intentions more strongly among liberals. Some inconsistent evidence also suggested that perceived nonpolitical dissimilarity was associated with prejudice and lower affiliative intentions more strongly among conservatives. These findings document nuance in relationships that could link ideological conflict to prejudice.